2014
DOI: 10.1117/12.2041208
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz spectroscopy of concrete for evaluating the critical hydration level

Abstract: Concrete, a mixture of cement, coarse aggregate, sand and filler material (if any), is widely used in the construction industry. Cement, mainly composed of Tricalcium Silicate (C3S) and Dicalcium Silicate (C2S) reacts readily with water, a process known as hydration. The hydration process forms a solid material known as hardened cement paste which is mainly composed of Calcium Silicate Hydrate (C-S-H), Calcium Hydroxide and Calcium Carbonate. To quantify the critical hydration level, an accurate and fast techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Once the C-S-H hardens at around 7 days, the Si-O bending modes become stiffer which varies the resonance peak resulting in decreased area. Similar trend has already been reported in the earlier work by the above authors 16 . For the above water-cement ratios, there is again a gradual dip around 20-21 days, which is because of the onset of reactions of C2S.…”
Section: Analysis Of the Formation Of Key Hydration Productssupporting
confidence: 86%
“…Once the C-S-H hardens at around 7 days, the Si-O bending modes become stiffer which varies the resonance peak resulting in decreased area. Similar trend has already been reported in the earlier work by the above authors 16 . For the above water-cement ratios, there is again a gradual dip around 20-21 days, which is because of the onset of reactions of C2S.…”
Section: Analysis Of the Formation Of Key Hydration Productssupporting
confidence: 86%
“…Based on THz spectra, Maruyama et al (71) determined that the lower frequencies of 0.1 and 0.05 THz are more appropriate for evaluating the moisture content of hardened cement paste due to the nonsensitivity to chemically bounded water that occurs at higher frequencies. Moreover, Dash et al (72) reported that THz spectroscopy is a promising tool to quantify the hydration process; that is, the time-dependent reaction of cement with water, which can significantly contribute to the improved understanding of the hydration kinetics of cement necessary to optimize the mechanical characteristics of concrete. Concerning the fact that THz sensing is able to detect the hazardous gases (24), another issue related to the contamination of concrete can be studied.…”
Section: Concrete Brick Sand Cement Stonementioning
confidence: 99%
“…[ [143][144][145][146] Asbestos & Rock Wool Analyse the existence of asbestos [118] It is not fortunate that long-term suffer in air asbestos fibers is not security to human beings and can lead to related asbestos diseases. Detect corrosion in the pipe [147] 7…”
Section: Thz Hollow Metal Waveguidementioning
confidence: 99%